2003
DOI: 10.1042/bj20030120
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic peptides derived from the prosegments of proprotein convertase 1/3 and furin are potent inhibitors of both enzymes

Abstract: Proprotein convertases (PCs) are Ca(2+)-dependent serine proteases of the subtilisin/kexin family which are known specifically to cleave propeptide and proprotein substrates at the C-terminal of R-X-(K/R)-R/ to generate the relevant biologically active peptides. PCs are initially synthesized as enzymically inactive proenzyme forms where the prosegments play an important inhibitory role to the respective enzymes. Here we investigated whether synthetic peptides derived from the pro-region could also represent sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 42 publications
3
38
0
Order By: Relevance
“…These roles, however, have not yet been fully understood, and further studies on various proteins are necessary. As for the inhibitory properties of the propeptides of peptidases, there are numbers of reports describing their inhibition profiles and type of inhibition (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, only a few attempts have been made so far to identify critical sequences and/or residues in the propeptide important for inhibition of the corresponding mature peptidase, and much of the inhibition mechanisms, the structural determinants in the propeptide, and the sites of binding involved in the inhibition remains to be established.…”
mentioning
confidence: 99%
“…These roles, however, have not yet been fully understood, and further studies on various proteins are necessary. As for the inhibitory properties of the propeptides of peptidases, there are numbers of reports describing their inhibition profiles and type of inhibition (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, only a few attempts have been made so far to identify critical sequences and/or residues in the propeptide important for inhibition of the corresponding mature peptidase, and much of the inhibition mechanisms, the structural determinants in the propeptide, and the sites of binding involved in the inhibition remains to be established.…”
mentioning
confidence: 99%
“…Furthermore, we and others have previously shown that synthetic peptides of various lengths did not exhibit any significant selectivity (14,17,19) nor did the isolated propeptides when assayed against a variety of convertases (19). However, single amino acid substitutions were shown to exhibit a profound effect on both inhibition and activation of convertases.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanism of Inhibition of PC1/3 Propeptide Mutants toward mPC1/3 and Human Furin-Synthetic inhibitory peptides against convertases, engineered from the COOH-terminal part, presented a competitive pattern of inhibition supporting the fact that this portion of the propeptide interacts directly with the active site (14,19). Upon elongating these peptides toward the NH 2 terminus, a change in inhibitory behavior was observed, because the initial competitive inhibition changed with the length of the peptide to mixed-inhibition and even FIGURE 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence our biosynthetic data and modelling support this concept, whereby a zymogen with a pro-region existing in a state of low affinity for its catalytic domain retains intrinsic enzymic activity. Interestingly, recent results obtained on the inhibitory properties of peptides derived from the pro-regions of PC1 and furin have demonstrated how residues His-66 and Phe-67 may well contribute to the affinity of pro-regions for the catalytic domains [40].…”
Section: Discussionmentioning
confidence: 99%